The joker : a memoir - Hudgins, Andrew
"Since Andrew Hudgins was a child, he was a compulsive joke teller, so when he sat down to write about jokes, he found that he was writing about himself--what jokes taught him and mistaught him, how they often delighted him but occasionally made him nervous with their delight in chaos and sometimes anger. Because Hudgins's father, a West Point graduate, served in the US Air Force, his family moved frequently; he learned to relate to other kids by telling jokes and watching how his classmates responded. And jokes opened him up to the serious, taboo subjects that his family didn't talk about openly--religion, race, sex, and death. Hudgins tells and analyzes the jokes that explore the contradictions in the Baptist religion he was brought up in, the jokes that told him what his parents would not tell him about sex, and the racist jokes that his uncle loved, his father hated, and his mother, caught in the middle, was ambivalent about. This book is both a memoir and a meditation on jokes and how they educated, delighted, and occasionally horrified him as he grew"--